2020
DOI: 10.1159/000506057
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effect of Short-Term Combined High-Intensity Interval Training on TLR4, NF-κB and IRF3 Expression in Young Overweight and Obese Girls

Abstract: Obesity is commonly associated with immunometabolic dysfunctions. Activation of inflammatory macrophages through TLR4 (toll-like receptor 4) and the anti-inflammatory impact of exercise have been and are the new concerns among researchers. A new short-term combined high-intensity interval training was proposed in young sedentary overweight/obese females. All participants were allocated to one of two groups: the exercise group (EG) and the control group (CG), where the EG participated in a 2-week combined train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
1
3
0
3
Order By: Relevance
“…TLR4 and NF‐kBp65 were downregulated in PBMCs after 12 weeks of combined exercise in people with T2D (Liu et al, 2015). Some short‐term HIIT (Robinson et al, 2015; Soltani et al, 2020), but not all (Oliveira‐Child et al, 2013), confirmed current results. Our findings revealed that adding RE to high‐demand exercise training, such as HIIT, can make this multi‐modal exercise more effective than uni‐modal at triggering anti‐inflammatory adaptations through additional mechanisms.…”
Section: Discussionsupporting
confidence: 79%
“…TLR4 and NF‐kBp65 were downregulated in PBMCs after 12 weeks of combined exercise in people with T2D (Liu et al, 2015). Some short‐term HIIT (Robinson et al, 2015; Soltani et al, 2020), but not all (Oliveira‐Child et al, 2013), confirmed current results. Our findings revealed that adding RE to high‐demand exercise training, such as HIIT, can make this multi‐modal exercise more effective than uni‐modal at triggering anti‐inflammatory adaptations through additional mechanisms.…”
Section: Discussionsupporting
confidence: 79%
“…Recent research has demonstrated that Gram-negative bacteria in the gut microbiota of obese people can create lipopolysaccharides (LPS) and bind to toll-like receptor 4 (TLR-4), activating nearby and distant pro-inflammatory cascades and releasing inflammatory factors (70, 71). TLR4 is an important binding regulator of LPS, which is overexpressed in intestinal mucosal epithelial cells after stimulation of activation, inducing the production of various proinflammatory factors and causing and maintaining obesity-type low-level inflammation in the body (72). In addition, damage to the intestinal mucosal barrier can also lead to inflammation.…”
Section: The Chronic Mild Inflammatory Responsementioning
confidence: 99%
“…Sendo assim, acredita-se na possibilidade de um tratamento baseado na inibição das vias de sinalização dos TLRs para supressão de respostas inflamatórias crônicas e que, ainda assim, mantenha a funcionalidade dos mesmos e a integridade do sistema imune inato (EL-ZAYAT; SIBAII; MANNAA, 2019). Neste sentido, é importante aprofundar o conhecimento sobre a interação entre as diferentes proteínas reguladoras negativas do TLR4, cuja ineficiência em modular as respostas da sinalização TLR4 parece estar relacionada ao desenvolvimento da meta-inflamação na obesidade (SOLTANI et al, 2020a).…”
Section: Mecanismos Relacionados à Expressão Gênicaunclassified
“…De qualquer forma, estes fatos indicam que as miocinas anti-inflamatórias produzidas pelos músculos esqueléticos podem alterar beneficamente o status inflamatório de células imunes, reduzindo a inflamação crônica mesmo sem redução da massa corporal (SOLTANI et al, 2020a). Por estes motivos, parecem ser um alvo terapêutico importante nos estudos sobre os mecanismos subjacentes às desordens metabólicas da obesidade, merecendo ser mais bem estudados.…”
Section: Mecanismos Relacionados à Expressão Gênicaunclassified